Investigating danger indicators in the soil samples of the Nile Region in Babylon Governorate in Iraq - Ibrahem, Salar Hussein (Edelweiss Applied Science and Technology, 2024)
This study was conducted to detect the presence of radionuclides in the Nile region, which is one of the districts affiliated with the Mahaweel district in the Babil Governorate in Iraq and is located to the southeast of the center of the district, where many cancer cases appeared in this area, which necessitated researching whether there is a trace of radioactivity in the soil of this region was used, where the “NaI(Tl) gamma detector” was used, and the activity concentration levels of 238U, 232Th, and 40K were measured and compared with the internationally permissible values for twenty samples of the soil of this region. The radionuclides of the soil were as follows: 238U with an average of (11.72±1.62) Bq/kg, 232Th with an average of (21.04±3.7) Bq/kg and 40 K with an average of (133.55±1.82). Bq/kg. Absorbed dose rate, annual effect, radium equivalent activity, effective dose rate (EDR), and equivalent dose (AEDE) were measured. The radioactivity level index (I), external (Hex) and internal (Hin) risk indices, as well as increased lifetime cancer risk (ELCR) were determined. It was concluded that there is no danger that may threaten the population in this area, and thus the possibility of any health effects of radiation is low. The values obtained are considered among internationally accepted values, meaning that this area is free of harmful radioactivity.